2004
DOI: 10.1021/la048967u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in Cationic Micelles upon Incorporation of a Polar Organic Dopant

Abstract: Micelles of cetyltrimethylammonium bromide (CTAB), when doped with increasing levels of 4-ethylphenol, show microstructural transitions from spherical micelles to elongated wormlike micelles, disks, and subsequently to globular and then to tubular vesicles. Wormlike micelles are observed at a dopant-to-CTAB molar ratio of 1:3. At higher dopant ratios (1:1), globular vesicles are observed which transition to tubular vesicles when the dopant becomes the predominant species at a ratio of 3:1. These transitions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…Changes in microstructure of surfactant aggregates that are induced by the addition of a series of phenolic organic dopants (phenol, cresol and alkyl-substituted phenols, namely 4-ethyl phenol, 4-n and i-butyl phenol) to a micellar solution of CTAB have been studied using cryogenic transmission electron microscopy (cryo-TEM) [61][62][63]. As the concentration of each of the dopants is increased, there is a systematic reduction in the curvature of the observed microstructure.…”
Section: Microstructural Transition Of Micelles In the Presence Of Nementioning
confidence: 99%
“…Changes in microstructure of surfactant aggregates that are induced by the addition of a series of phenolic organic dopants (phenol, cresol and alkyl-substituted phenols, namely 4-ethyl phenol, 4-n and i-butyl phenol) to a micellar solution of CTAB have been studied using cryogenic transmission electron microscopy (cryo-TEM) [61][62][63]. As the concentration of each of the dopants is increased, there is a systematic reduction in the curvature of the observed microstructure.…”
Section: Microstructural Transition Of Micelles In the Presence Of Nementioning
confidence: 99%
“…The design of new materials, especially nanomaterials based on self-organization procedure has been one of the main focus in the field of supramolecular chemistry. 2 There is a multitude of interesting structures including micelles with different sizes and shapes, 3 bilayer vesicles 4,5 and liquid-crystalline mesophases 6 that are formed during interactions of amphiphiles. Previous studies have also reported formation of ribbons, 7,8 disks, 9 and gel-like crystalline mesophases that are used to template materials in both aqueous and/or nonaqueous domains.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies using a variety of techniques such as rheological approaches, [7][8][9][10][11][12] birefringence, 8 NMR, 4,5,8,13,14 heat capacity, 15 acidity, 13 neutron reflectivity, 6 surface tension, 16 and SANS measurements 4,17,18 have been performed on the influence of organic counterions on cationic surfactants. It has been demonstrated that aromatic counterions are more effective at lower concentrations than salts or electrolytes in inducing the micellar growth, 6,13,19 which can be attributed to interactions with the aromatic π-electron system.…”
Section: Introductionmentioning
confidence: 99%
“…13 Particularly aromatic anions like hydroxyand chlorobenzoates and phenols have been investigated for inducing the elongation of CTAB micelles. [4][5][6]9,11,12,18,20,21 Substituents and their position on the aromatic ring system play an important role in micellar growth. While hydroxyl groups in the ortho-position induce growth, those in the para-and meta-position do not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation